Neoproterozoic magmatic arc systems of the central Ribeira belt, SE-Brazil, in the context of the West-Gondwana pre-collisional history: A review. (November 2020) - Heilbron, Monica; de Morisson Valeriano, Claudio; Peixoto, Caroline; Tupinambá, Miguel; Neubauer, Franz; Dussin, Ivo; Corrales, Felipe; Bruno, Henrique; Lobato, Marcela; Horta de Almeida, Julio Cesar; Guilherme do Eirado Silva, Luiz
Abstract: This synthesis presents the complex evolution of two different magmatic arc systems in the Ribeira belt, which were progressively accreted onto the southeastern and southern border of the São Francisco paleocontinent. The Inner Magmatic Arc System, developed between ca. 650 and 595 Ma within a Paleoproterozoic microcontinent, is presently represented by the Socorro, Marceleza-Leopoldina and Serra da Bolívia arcs, and possibly by arc-related rocks within the Embú terrane. The Inner Magmatic Arc System collided against the southeastern margin of the São Francisco (SFC) paleocontinent at ca. 600 Ma, at about the time of the emplacement of syn-collisional granitoid rocks into the lower plate. Few inherited zircons of Tonian age and one description of a Tonian body related with the Embú Complex could indicate that subduction of the Inner Magmatic Arc System started earlier in the southern Ribeira belt. On the other hand, the Outer Magmatic Arc System comprises the rocks of the Serra da Prata and Rio Negro magmatic arcs. The available geochemical, geochronological and isotopic data of magmatic rocks indicate a two-stage evolution with an intra-oceanic arc setting for the first stage between ca. 860-760, and a Japan-style tectonic setting for the ca. 640-605 Ma s stage. Within both stages, a geochemical polarity that pointed to east-verging subduction has been documented, as well as a lack of older basement rocks in the outer arc domain. During this period of subduction, the Outer Magmatic Arc System produced a considerable volume of Neoproterozoic juvenile addition to the crust. If considered together with other examples of West-Gondwana, the Neoproterozoic magmatic arc development testifies a dynamic scenario until the final docking onto the SFC paleocontinent. Finally, the pre-collisional magmatic evolution envisaged here for the Ribeira belt is very similar in time and composition to that of the Goiás Magmatic Arc, in the Brasilia orogenic belt of central Brazil, as first proposed by Márcio Pimentel and co-workers. Graphical abstract: Image 1 Highlights: Two magmatic arc systems were progressively accreted onto the southeastern border of the São Francisco paleocontinent. The ca. 650-595 Ma continental Inner Arc and basins developed onto dismembered microcontinents with Paleoproterozoic basement. The Outer Arc comprises the juvenile intra-oceanic stage (ca.860-769 Ma) and a younger Japan style stage (ca. 790-620 Ma). Fore-arc and back arc basins were developed coevally to the two stages of the OuterArc. The presence of two magmatic arc systems indicates a complex and diachronic subduction evolution.